Biventricular pacemaker implantation via a persistent left superior vena cava after removal of an infected device from the right side. Issue 4 (30th May 2019) - Yamamoto, Tasuku; Goya, Masahiko; Ando, Kenji; Yagishita, Atsuhiko; Maeda, Shingo; Hirao, Kenzo
Abstract: Persistent left superior vena cava (PLSVC) is a congenital anomaly that poses a unique challenge when implanting cardiac implantable electronic devices (CIEDs) from the left side. To date, only a few isolated case reports are available regarding biventricular pacemaker implantation via PLSVC. These reports lack procedural details and tips to overcome difficulties faced by the physician when performing this technically demanding procedure. In the present report, we describe a patient who successfully underwent biventricular pacemaker implantation via a PLSVC after transvenous extraction of an infected device from the contralateral side, and discuss the technical implications.